A Review the Development of Infection Prevention and Control Program in Nursing Care During Covid-19 Pandemic - Candra Dewi Rahayu; Diah Fitri Purwaningsih; Ika Silvitasari (GLOBAL HEALTH SCIENCE GROUP, 2021)
The hospital is the health service structure that plays the most prominent role with the Covid-19 pandemic.The nursing profession is still required to provide quality nursing care to Covid-19 patients, as well as to other patients so that the provision of nursing care must be in accordance with the procedures and management of patients with infectious diseases accurately and correctly and use Personal Protection Equipment in accordance with standard. Infection prevention and control during the pandemic is very important for patients and health workers to minimize the occurrence of nosocomial infections during hospital care. This review aims to determine the development of infection prevention and control program in the provision of nursing care during the Covid-19 pandemic. The research method with a review was carried out by searching for articles related to patient safety in providing Covid-19 nursing care. Literatures search were carried out in December 2020 - January 2021 through PubMed, Sciencedirec, google scholar, government policy then entered the online database list by entering keywords, namely patient safety, nursing care, Covid-19. Selected journals were based on inclusion and exclusion criteria through a critical assessment process with CASP to assess the quality of articles. The results of the critical appraisal obtained six articles that match the inclusion criteria with a minimum appraisal score of 85 in good categories which are then carried out by analysts. The results of the research by reviewing 6 articles show that prevention and control of patients safety in providing nursing care during a pandemic can be developed through nursing care management by using summarized checklists, patient safety-based nursing care service system, infection prevention and control during the pandemic and inclusive leadership. Nursing care management, patient safety, infection prevention and control and an inclusive leadership style are the development methods that can be used for the prevention and control of Covid-19.